2021
DOI: 10.3389/fevo.2021.724887
|View full text |Cite
|
Sign up to set email alerts
|

The Cognitive Ecology of Animal Movement: Evidence From Birds and Mammals

Abstract: Cognition, defined as the processes concerned with the acquisition, retention and use of information, underlies animals’ abilities to navigate their local surroundings, embark on long-distance seasonal migrations, and socially learn information relevant to movement. Hence, in order to fully understand and predict animal movement, researchers must know the cognitive mechanisms that generate such movement. Work on a few model systems indicates that most animals possess excellent spatial learning and memory abili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 307 publications
(392 reference statements)
0
25
0
Order By: Relevance
“…Competition may moreover have qualitative effects on the relationship between environmental heterogeneity and fitness (Trevail et al, 2019). At the same time, social information, gained by following or monitoring competitors, plays a major role in the cognitive movement ecology of many species (Kashetsky et al, 2021), and may have non-trivial interactions with the effects of cognitive biases. Lastly, the presence of other individuals with different cognitive strategies (e.g., different levels of optimism) could potentially play an important role in the evolution of an optimal cognitive strategy, and hence the formation of a cognitive niches, via either density-or frequency-dependent selection (Beecham, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Competition may moreover have qualitative effects on the relationship between environmental heterogeneity and fitness (Trevail et al, 2019). At the same time, social information, gained by following or monitoring competitors, plays a major role in the cognitive movement ecology of many species (Kashetsky et al, 2021), and may have non-trivial interactions with the effects of cognitive biases. Lastly, the presence of other individuals with different cognitive strategies (e.g., different levels of optimism) could potentially play an important role in the evolution of an optimal cognitive strategy, and hence the formation of a cognitive niches, via either density-or frequency-dependent selection (Beecham, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Models have shown that collective knowledge is important, if not essential, to the evolution and process of migration (Guttal and Couzin, 2010;Shaw and Couzin, 2013;Berdahl et al, 2018). Many migratory organisms are social, and social learning is an acknowledged, non-genetic method for transmitting information (Kashetsky et al, 2021). Furthermore, the general role of social learning for improving a population's ability to track resources has been studied not just in animal systems, but in synthetic systems inspired by social behavior of animals such as optimization heuristics algorithms and the study of swarm robotics (Şahin, 2005;Brambilla et al, 2013).…”
Section: Social Learning and Collective Knowledgementioning
confidence: 99%
“…However, behaviorally plastic migrants, particularly long-distance migrants, are likely making migratory decisions with less than complete knowledge of the habitat at their destination. Cognition, the processes concerned with the acquisition, retention, and use of information (Dukas, 1998(Dukas, , 2004Kashetsky et al, 2021), is the lens through which an individual comes to understand its physical environment. Therefore, migratory behavior arises from an individual's 'informational state'-knowledge of its current and alternative environments, rather than the attributes of the environment itself (Blumstein and Bouskila, 1996;Avgar et al, 2013;Merkle et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…An individual's knowledge of its environment may result from previous experience, which when encoded in the brain and retained over time is called memory (Fagan et al, 2013;Kashetsky et al, 2021). Memory encompasses two forms of information: an individual's experience of its physical environment (attribute memory) and the spatial location associated with that experience (spatial memory) (Fagan et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation